Institutions and forest management: A case study from Swat, Pakistan - Gideon Kruseman; Lorenzo Pellegrini (Fondazione Eni Enrico Mattei (FEEM), 2008)
Deforestation in the North western part of Pakistan is a long standing problem. The Forestry Department, as formal managers of the forest resources, has been undergoing a long reform process aimed at improving its performance. This reform process has not resulted in less deforestation. From the policy perspective this has been leading to stated intentions to further reform the Forestry Department, the question is whether organizational reform is the answer. We think there are more limiting bottlenecks to sustainable forest management in Pakistan. De facto property rights are not as simple as denoted by statutory law. In this article we explore the mechanisms behind the deforestation and try to uncover mechanisms to reverse the process. Although our conclusions are not very optimistic, we provide a framework for determining the bottlenecks in the management of common resources from the perspective of institutions. We show that in circumstances where institutional change is necessary we are faced with a trade-off between the transaction costs related to the enforcement of 'improved' institutional arrangements and the transaction costs improving enforceable institutional arrangements. Incurring these transaction costs only makes sense if the benefits from improved institutional arrangements outweigh them and the transition costs. When we relate this dilemma to the management regime of the forest in North west Pakistan, we identify at the one end of the spectrum the ideal forest management system; at the other end we see the spontaneous evolution of self organization. The current situation is an intermediate form with an incoherent set of external interventions and strategic reactions by different agents in the local communities. The emergent system of management is the one producing the present dismal outcome.
Keywords: Q23; Q58; 330; New institutional Economics; Corruption; Forestry; Swat; Abholzung; Forstpolitik; Korruption; Neue Institutionenökonomik; Swat; Pakistan